Enzymatic hydrolysis of Swietenia macrophylla wood chips with modified sulfite pretreatment to overcome recalcitrance of lignocellulose (SPORL). - Roque, Eugeio S. III
This study evaluated the potential feedstock of Swietenia macrophylla to cellulosic bioethanol production using sulfite pretreatment to overcome recalcitrance of lignocellulose (SPORL) as pretreatment. The analysis of the composition of Swietenia macrophylla, or mahogany, showcased its potential as a cellulose-rich biomass for bioethanol production. It was revealed that untreated Swietenia macrophylla wood chips are composed of 38.8% cellulose, 36.2 hemicellulose, and 25.0 lignin (20.6% K. lignin and 4.4% acid-soluble lignin). In order to maximize the glucose yield in the subsequent enzymatic hydrolysis, S. macrophylla was pretreated with SPORL under different acid charge (0-0.22%) and bisulfite charge (1-4%) and with dilute acid for comparison. SPORL treatment resulted in a removal of 25.87 and 44.18% of lignin, degraded 11.26 to 30.68% of hemicellulose, and retained about 58.12 to 76.33% of cellulose after pretreatment. Results showed that at bisulfite charge of 1% without the addition of acid at 121 °C for 30 minutes. 34.3% of glucose yield was achieved. Dilute acid pretreatment only achieved 14%. Acid charge or pH of the pretreatment liquor play a significant role in enhancing digestibility of SPORL substrate however, its interaction with bisulfite charge has negative effect on glucose yield. These findings underscore the efficacy of SPORL, particularly at specific conditions, in maximizing glucose yield from Swietenia macrophylla, shedding light on optimization strategies for efficient bioethanol production from this promising biomass source.